1997
DOI: 10.1093/bja/78.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuates formation of lipid peroxides in tourniquet-induced ischaemia-reperfusion injury.

Abstract: We studied 20 adult ASA I patients undergoing elective peripheral surgery allocated randomly to one of two groups. In the propofol group (n = 9) anaesthesia was induced with propofol and fentanyl followed by continuous infusion of propofol. In the control group (n = 11), after induction of anaesthesia with thiopentone and fentanyl, anaesthesia was maintained with isoflurane. Concentrations of lipid peroxides in both plasma and muscle tissue samples were measured as thiobarbituric acid-reacting substances (TBAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 7 publications
(6 reference statements)
1
48
0
2
Order By: Relevance
“…Therefore, α-GST is considered to be a more sensitive marker of acute hepatic damage and its recovery than either AST or ALT [10,11]. (2) Plasma lipid peroxides were measured both to evaluate oxidative stress, which is one of the underlying mechanisms for IRI, and to enable the inhibitory effect of anesthetics on this stress to be evaluated [12,13]. Oxygen radicals, which cause cell damage via lipid peroxidation, are considered to be generated during liver ischemia-reperfusion [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, α-GST is considered to be a more sensitive marker of acute hepatic damage and its recovery than either AST or ALT [10,11]. (2) Plasma lipid peroxides were measured both to evaluate oxidative stress, which is one of the underlying mechanisms for IRI, and to enable the inhibitory effect of anesthetics on this stress to be evaluated [12,13]. Oxygen radicals, which cause cell damage via lipid peroxidation, are considered to be generated during liver ischemia-reperfusion [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Aarts et al has reported that propofol has a preventive role in cases such as coronary artery transplantation surgery, sepsis and burns, which of all lead into a decreased ontioxidising defense mechanism [13]. Also in some recent studies propofol has been reported to be a free radical scavenger due to its antioxidising property at anesthetic doses [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…4 A significant increase in MDA levels have been observed in the lung tissue during systemic inflammation induced by sepsis 22 and in plasma during lower-limb IR in patients. 5 The generation of MDA is believed to originate in the inflammatory cells. 4 In our study, the significant rise in plasma TBARS level in the T group compared with baseline values and not in the IP-T group supports the supposition that a lipid peroxidation process occurs during IR, and the IP attenuates this process.…”
Section: Discussionmentioning
confidence: 99%
“…4 Significant increase in TBARS level has been observed in the plasma of patients undergoing lower-limb IR. 5 Ischaemic preconditioning (IP) is defined as a brief period of ischaemia followed by tissue perfusion, thereby increasing ischaemic tolerance of tissue for a subsequent longer ischaemic period. This phenomenon was first described by Murry et al, 6 in a canine model of myocardial ischaemia.…”
Section: Introductionmentioning
confidence: 99%